2017
DOI: 10.3389/fneur.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Calcitonin Gene-Related Peptide Increases Cerebral Vessel Diameter in Animal Models of Subarachnoid Hemorrhage: A Systematic Review and Meta-analysis

Abstract: Delayed cerebral ischemia (DCI) is a life-threatening complication after subarachnoid hemorrhage. There is a strong association between cerebral vessel narrowing and DCI. Alpha calcitonin gene-related peptide (αCGRP) is a potent vasodilator, which may be effective at reducing cerebral vessel narrowing after subarachnoid hemorrhage (SAH). Here, we report a meta-analysis of data from nine in vivo animal studies identified in a systematic review in which αCGRP was administered in SAH models. Our primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…While the least dilution (greatest concentration) of the BOXes mixture caused dilation and the greatest dilutions lacked both constrictor and dilator efficacy, intermediate dilutions caused constriction ( Clark et al, 2002 ; vehicle controls not reported). The constriction was relatively slow to develop, i.e., 40 min, and was still present at 24 h ( Clark et al, 2002 ), consistent with the prolonged vasospasm observed with SAH ( Crowley et al, 2008 ; Siasios et al, 2013 ; Flynn et al, 2017 ; Geraghty and Testai, 2017 ).…”
Section: Exogenous Boxessupporting
confidence: 67%
See 2 more Smart Citations
“…While the least dilution (greatest concentration) of the BOXes mixture caused dilation and the greatest dilutions lacked both constrictor and dilator efficacy, intermediate dilutions caused constriction ( Clark et al, 2002 ; vehicle controls not reported). The constriction was relatively slow to develop, i.e., 40 min, and was still present at 24 h ( Clark et al, 2002 ), consistent with the prolonged vasospasm observed with SAH ( Crowley et al, 2008 ; Siasios et al, 2013 ; Flynn et al, 2017 ; Geraghty and Testai, 2017 ).…”
Section: Exogenous Boxessupporting
confidence: 67%
“…Additionally, the effect of BOXes was slow to reverse ( Hou et al, 2011 ). These findings of Hou et al (2011) are consistent with the ability of BOXes to traverse the membrane to act at a cytoplasmic site of Slo1 K + channels and, further, the sustained constriction following supradural application of BOXes ( Clark et al, 2002 ), the resistance to reversal of the constriction of cerebral vessels in brain slices (see below; Joerk et al, 2014 ), and the prolonged vasospasm following SAH ( Crowley et al, 2008 ; Siasios et al, 2013 ; Foreman, 2016 ; Flynn et al, 2017 ; Geraghty and Testai, 2017 ). In addition to a direct inhibitory effect of BOXes on Slo1 K + channels ( Hou et al, 2011 ), BOXes activation of protein kinase C ( Pyne-Geithman et al, 2008 ) may represent an additional signaling pathway for Slo1 K + channel inhibition.…”
Section: Exogenous Boxessupporting
confidence: 66%
See 1 more Smart Citation
“…Orexin-A exerts its functions by binding its receptors, Orexin-1 receptor (Ox1) and Orexin-2 receptor (Ox2), two G-protein coupled receptors [ 18 , 19 , 20 ]. The Orexin system is involved in physiological and pathophysiological processes [ 21 , 22 , 23 ] ( Figure 1 B). Many metabolic molecules influence Orexin-A activity; in particular, glucose, leptin, and amino acids and also some environmental factors increase Orexin-A levels during the waking phase of the circadian cycles and fasting or periods of caloric restriction.…”
Section: Orexin-a: General Characteristicsmentioning
confidence: 99%
“…The relationship between sleep disturbance and migraine/headache could involve another fundamental neurobiological system, the orexin/hypocretin system, which seems to play a key role in regulating both the sleep/wake cycle and REM sleep ( 35 ), and it may also be associated with migraine pathogenesis. Indeed, orexin/hypocretin A and orexin/hypocretin B are hypothalamic excitatory neuropeptides that, in addition to regulating sleep/wake rhythm, play a role in many biological pathways involved in thermoregulation, energy metabolism control, mood and emotional regulation, energy homeostasis, reward mechanisms, drug dependence, cardiovascular responses, sexual behavior, nutritional behavior, and spontaneous physical activity ( 36 38 ). It is interesting to note that some symptoms associated with migraine such as tiredness, yawning, drowsiness, and desire for certain foods may be due to an involvement of the orexin/hypocretin system.…”
Section: Introduction/background Of Migraine and Non-rapid Eye Movemementioning
confidence: 99%